T2 Dark Bands on Placental MRI as a Potential Predictor of The Severity of Post-Partum Hemorrhage in Placenta Adhesion Disorders - Nadia Rahaim,; Elspeth Whitby, (AlQalam Journal of Medical and Applied Sciences, 2025)
Placenta adhesion disorders (PAD) are increasingly encountered in obstetric practice due to the increase in caesarean section deliveries and placenta previa rate. If a case is confronted unexpectedly, the result is massive blood loss, which cannot be managed optimally unless identified in the antenatal period. This study was conducted to assess the value of placental dark bands in T2 W images in predicting the severity of hemorrhage at delivery. Retrospective analysis of clinical data and magnetic resonance imaging (MRI) for 55 women who underwent pelvic MRI scans between February 2010 and October 2013 due to risk factors for placental adhesion. The frequency of delivery complications was higher in cases with T2 dark bands in comparison with that with no bands {blood loss (ml) median (25,75) 1500(500-3500) vs 550(400-1000), P=0.006; blood transfusion(ml) median (25,75) 1500(0-4200 vs 0(0,0), P=0.003; length of stay in hospital (days) median (25,75) 3(2-6) vs 2.5(2-3), P=0.02}. The median blood loss was higher in women with T2 multiple dark bands (3000 ml) compared to those with single dark bands (550 ml). Placenta previa (PP) was a cofactor for bleeding (PP present associated with blood loss mean ± SEM 2877.3± 525.6 vs 1441.9± 353.7 when PP absent, the difference in means [95%CI] 1435.4[-2692.5- -178.3] P=0.026). However, multiple bands are an independent factor for maternal bleeding as the amount of blood loss increases with the number of bands, irrespective of the presence or absence of PP. PAD is associated with severe blood loss and blood transfusion. T2 Dark bands have the potential ability to predict the severity of hemorrhage at delivery.